Harmonisasi Peraturan Perlindungan Hukum bagi Investor di Pasar Modal - Rahma Donna; Sintong Arion Hutapea (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This study aims to analyze the legal protection for investors in the capital market through the harmonization of existing regulations. In the context of Indonesia's capital market, legal protection is a crucial aspect for maintaining investor confidence and creating a healthy investment climate. Although various regulations, such as Law No. 8 of 1995 on Capital Markets, have been established, the implementation of legal protection still faces several challenges, including a lack of alignment between existing regulations. This research employs a normative approach with legal analysis and literature review as data collection methods. The findings indicate that regulatory harmonization is essential to enhance the effectiveness of legal protection for investors, both preventively and repressively. With harmonization in place, it is expected that regulations can operate more effectively and provide better protection for investors in the capital market.